Screening of Rapeseed Genotypes against Alternaria blight - Toppo, Papiya Clara; Hossain, SK. Md. Mobarak; Hasan, Md. Mahfuzul; Rashid, Md. Mamunur; Hossain, Afsana; Jui, Jannatun Nahar; Karim, Fatima (Journal of Agricultural Sciences (Belgrade), 2025)
Alternaria blight is a destructive fungal disease that infects rapeseed leaves and siliqua. The purpose of this study is to evaluate the disease severity of various mustard genotypes and to identify the superior rapeseed genotypes that are resistant to Alternaria blight. Twelve rapeseed genotypes were investigated.  At 45, 55, and 65 days after sowing (DAS), genotype NAP16061 showed the lowest disease severity (12.43%, 15.06%, and 11.06%, respectively). NAP16001 had the fewest diseased pods (1.000, 1.133, and 1.700, respectively) at 45, 55, and 65 DAS, respectively. In terms of the quantities of healthy pods, NAP16001, NAP16068, and NAP16068 performed better. BARI SH 13 had the lowest total numbers of leaves plant-1 and percent leaf area, while NAP16061 had the smallest average spot size on leaves. The greatest plant height was observed in NAP16066. Positive loadings for disease susceptibility parameters such as disease severity, percent disease severity, percent leaf area diseased, and diseased leaves plant-1 were observed in PC1. NAP16066, NAP16025, and NAP16001 showed a negative relationship with PC1, indicating resistance to Alternaria blight. Genotypes such as NAP16082 and NAP16068 were also negatively oriented along PC2, exhibited moderate resistance, requiring further assessment. Cluster II includes the most sought-after genotypes with resistance to Alternaria blight disease, which clustered with NAP16001 and NAP16066.